Sport leadership in the 21st century - Burton, Laura J.; Borland, John F.; Kane, Gregory M. (Jones & Bartlett Learning, 2020)
All organizations look to leaders to influence and motivate employees in working toward organizational goals and future success, and that includes sports organizations. Sport Leadership in the 21st Century, second edition provides students with the most current and comprehensive understanding of leadership in sport management. Authored and contributed by leading sport management researchers and practitioners, this text immerses students in the learning process through case studies, interviews with leaders in the sport industry, critical thinking questions, and rich content. Each chapter has been developed to provide the latest research to help young professionals and sport management students become leaders in different areas of sport